The business case for corporate training applications of Web-based tele-learning. - Whalen, Tammy. (University of Ottawa (Canada), 1999)
The Business Case for Corporate Training Applications of Web-Based Tele-Learning is divided into five chapters, each illustrating a key concept related to the economic and business impacts of implementing Web-based training in corporations. Chapter 1, the "Market for Web-Based Tele-Learning" presents an overview of the Web-based training industry and includes many examples of how corporations are using Web-based training today. The costs and benefits of Web-based training are introduced, including online training management. Chapter 2, "Cost-Benefit Analysis of Web-Based Tele-Learning: Case Study of the Bell Online Institute" hypothesizes that there are several key design elements that must be considered in costing Web-based training projects. The relative importance of these elements is examined using a case study approach. Chapter 3, "Web-Based Competency and Training Management Systems for Distance Learning" discusses the value to companies of using a Web-based system for competency and training management, using the case of Bell Canada as an example of how companies are implementing these tools today. Chapter 4, "Pricing Models for Web-Based Tele-Learning" examines the factors that influence the pricing of Web-based courses for employee training. Chapter 5, "Business Process Reengineering for the Use of Distance Learning at Bell Canada" is a case study that examines the use of Web-based training at Bell Canada in the context of business process reengineering. (Abstract shortened by UMI.)
Keywords: Education, Adult and Continuing.